A case study of repetitive transcranial magnetic stimulation for cryptococcal meningitis combined with cognitive impairment - Liu, Yuanbiao; Fan, Lei; Jiang, Xinlin; Lu, Yi; Li, Yige (Frontiers in Human Neuroscience, 2022)
Cryptococcal meningitis (CM) is a central nervous system disease caused by a novel Cryptococcus infection that leads to subacute or chronic inflammatory changes in the nervous system. In this study, we present the case of a woman aged 72 years with CM and severe cognitive impairment and disabilities. The cognitive assessment indicated that, although her cognitive function was impaired, especially executive function, it largely improved after receiving anti-infectious and repetitive transcranial magnetic stimulation, which can alter the membrane potential of the cortical nerve cells by triggering long-term potentiation and depression, modulating and releasing hormones, reducing the level of neuroinflammatory and peripheral blood cytokines, promoting nerve regeneration and synaptic remodeling, and changing the activity of the neural circuitry of the dorsolateral prefrontal cortex. We argue that this case provides a novel method of treatment for patients with CM in conjunction with cognitive impairments.